Updates on Age to Start and Stop Colorectal Cancer Screening: Recommendations From the U.S. Multi-Society Task Force on Colorectal Cancer. (15th January 2022) - Patel, Swati G.; May, Folasade P.; Anderson, Joseph C.; Burke, Carol A.; Dominitz, Jason A.; Gross, Seth A.; Jacobson, Brian C.; Shaukat, Aasma; Robertson, Douglas J.
Abstract : This document is a focused update to the 2017 colorectal cancer (CRC) screening recommendations from the U.S. Multi-Society Task Force on Colorectal Cancer, which represents the American College of Gastroenterology, the American Gastroenterological Association, and the American Society for Gastrointestinal Endoscopy. This update is restricted to addressing the age to start and stop CRC screening in average-risk individuals and the recommended screening modalities. Although there is no literature demonstrating that CRC screening in individuals under age 50 improves health outcomes such as CRC incidence or CRC-related mortality, sufficient data support the U.S. Multi-Society Task Force to suggest average-risk CRC screening begin at age 45. This recommendation is based on the increasing disease burden among individuals under age 50, emerging data that the prevalence of advanced colorectal neoplasia in individuals ages 45 to 49 approaches rates in individuals 50 to 59, and modeling studies that demonstrate the benefits of screening outweigh the potential harms and costs. For individuals ages 76 to 85, the decision to start or continue screening should be individualized and based on prior screening history, life expectancy, CRC risk, and personal preference. Screening is not recommended after age 85.